Development Online Training Media to Improve the Digital Marketing Competence of MSME Medan - Andrian, Andrian; Siregar, Efrizal; Ika Agustina; Reniwati Lubis; Khairil Anwar; Murtopo; Gunawan; Herri Trisna Frianto (Bahasa Indonesia, 2024)
The development of online media training for digital marketing training for small and medium enterprises (SMEs) in Medan aims to increase understanding and skills in digital marketing strategies to improve competitiveness and business sustainability in the digital era. The advantages of online media training include ease of access, cost efficiency, and scalability that allows reaching more participants simultaneously. The implementation of online media training is expected to increase participants' knowledge and skills, improve the quality of SME products and services, and increase the effectiveness of digital marketing. The research findings show that online media training provides benefits in improving the competitiveness and business growth of SMEs in Medan. Recommendations include wider promotion, periodic evaluation, development of relevant content, and expert involvement to continue to enhance the positive contribution of online media training in improving SMEs' competencies in digital marketing.